Are preoperative oral antibiotics effective in reducing the incidence of anastomotic leakage after colorectal cancer surgery? Study protocol for a prospective, multicentre, randomized controlled study - Rui Qi Gao; Wei Dong Wang; Peng Fei Yu; Zhen Chang Mo; Dan Hong Dong; Xi Sheng Yang; Xiao Hua Li; Gang Ji (Trials, 2022)
Abstract Introduction The optimal preoperative preparation for elective colorectal cancer surgery has been debated in academic circles for decades. Previously, several expert teams have conducted studies on whether preoperative mechanical bowel preparation and oral antibiotics can effectively reduce the incidence of postoperative complications, such as surgical site infections and anastomotic leakage. Most of the results of these studies have suggested that preoperative mechanical bowel preparation for elective colon surgery has no significant effect on the occurrence of surgical site infections and anastomotic leakage. Methods/design This study will examine whether oral antibiotic bowel preparation (OABP) influences the incidence of anastomotic leakage after surgery in a prospective, multicentre, randomized controlled trial that will enrol 1500 patients who require colon surgery. The primary endpoint, incidence of anastomotic leakage, is based on 2.3% in the OABP ± mechanical bowel preparation (MBP) group in the study by Morris et al. Patients will be randomized (1:1) into two groups: the test group will be given antibiotics (both neomycin 1 g and metronidazole 0.9 g) the day before surgery, and the control group will not receive any special intestinal preparation before surgery, including oral antibiotics or mechanical intestinal preparation. All study-related clinical data, such as general patient information, past medical history, laboratory examination, imaging results, and surgery details, will be recorded before surgery and during the time of hospitalization. The occurrence of postoperative fistulas, including anastomotic leakage, will be recorded as the main severe postoperative adverse event and will represent the primary endpoint. Ethics and dissemination Ethics approval was obtained from the Chinese Ethics Committee of Registering Clinical Trials (ChiECRCT20200173). The results of this study will be disseminated at several research conferences and as published articles in peer-reviewed journals. Protocol was revised on November 22, 2021, version 4.0. Trial registration ChiCTR2000035550 . Registered on 13 Aug 2020.